MEDICAL AND SOCIAL CHARACTERISTICS OF MODERN INFERTILE WOMEN ACCORDING TO THE REGISTRY OF INFERTILITY COUPLES IN THE TRANSBAIKAL REGION - Татьяна Евгеньевна Белокриницкая; Наталия Ивановна Фролова; Дмитрий Владимирович Малько (Мать и дитя в Кузбассе)
Aim – to identify medical and social factors of infertility in women living in the Trans-Baikal Territory.